2006
DOI: 10.1051/0004-6361:20053794
|View full text |Cite
|
Sign up to set email alerts
|

Accurate magnetic field measurements of Vega-like stars and Herbig Ae/Be stars

Abstract: We obtained accurate circular spectropolarimetric observations of a sample of Vega-like and Herbig Ae/Be stars with FORS 1 at the VLT in an attempt to detect their magnetic fields. No magnetic field could be diagnosed in any Vega-like star. The most accurate determination of a magnetic field, at 2.6 σ level, was performed for the Vega-like star ι Cen, for which we measured B z = −77 ± 30 G. In the prototype of Vega-like stars, the star β Pictoris, which shows conspicuous signs of chromospheric activity, a long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
78
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 41 publications
13
78
2
Order By: Relevance
“…A second detection in HD 139614 ( B z = −116 ± 34 G) was claimed by Hubrig et al (2006c), who also confirmed their previous measurement of −450 G. Later, Hubrig et al (2007a) revised both FORS1 observations, and reported B z − 112 ± 36 G and B z = −93 ± 14 G, for the first and the second measurement, respectively. A magnetic field was not detected in a third FORS1 measurement reported by Hubrig et al (2009c).…”
Section: Herbig Aebe Starssupporting
confidence: 61%
See 1 more Smart Citation
“…A second detection in HD 139614 ( B z = −116 ± 34 G) was claimed by Hubrig et al (2006c), who also confirmed their previous measurement of −450 G. Later, Hubrig et al (2007a) revised both FORS1 observations, and reported B z − 112 ± 36 G and B z = −93 ± 14 G, for the first and the second measurement, respectively. A magnetic field was not detected in a third FORS1 measurement reported by Hubrig et al (2009c).…”
Section: Herbig Aebe Starssupporting
confidence: 61%
“…Further surveys of Herbig AeBe stars using FORS1 were described by Hubrig et al (2006c) and Hubrig et al (2007a). Altogether, these papers reported the discovery of a magnetic field in three Herbig stars: HD 31648, HD 144432, and HD 144668.…”
Section: Herbig Aebe Starsmentioning
confidence: 96%
“…The results of the spectropolarimetric observations of the two Herbig Ae stars HD 31648 and HD 190073 with FORS 1 at a resolution of R ≈ 4000 turned out to be especially remarkable (Hubrig et al 2006a;Hubrig et al 2007a). These two stars possess almost the same effective temperature, but are different in luminosity and projected rotation velocity.…”
Section: Introductionmentioning
confidence: 96%
“…6 and following). Hubrig et al (2006Hubrig et al ( , 2009) reported a longitudinal magnetic field of 84±30 Gauss, up to 104±19 Gauss, while CAT found a longitudinal field of 74±10 Gauss.…”
Section: Introductionmentioning
confidence: 97%